2018
DOI: 10.1002/cphc.201800002
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Self‐Degradation Mechanisms in Methylammonium Lead Iodide Perovskites in Dark and Vacuum

Abstract: Organic-inorganic lead halide perovskite phases segregate (and their structures degrade) under illumination, exhibiting a poor stability with hysteresis and producing halide accumulation at the surface.In this work, we observed structural and interfacial dissociation in methylammonium lead iodide (CH NH PbI ) perovskites even under dark and vacuum conditions. Here, we investigate the origin and consequences of self-degradation in CH NH PbI perovskites stored in the dark under vacuum. Diffraction and photoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 52 publications
(66 reference statements)
2
50
0
Order By: Relevance
“…We propose that upon exposure to vacuum, the 2D perovskites are first degraded into PbI 2 , which further decomposes into metallic lead and volatile I − 2 ions. It is noteworthy that similar formation of metallic lead was also observed for 3D perovskites when exposed to vacuum conditions (Gunasekaran et al, 2018).…”
Section: Dynamics Of Degradationsupporting
confidence: 68%
See 1 more Smart Citation
“…We propose that upon exposure to vacuum, the 2D perovskites are first degraded into PbI 2 , which further decomposes into metallic lead and volatile I − 2 ions. It is noteworthy that similar formation of metallic lead was also observed for 3D perovskites when exposed to vacuum conditions (Gunasekaran et al, 2018).…”
Section: Dynamics Of Degradationsupporting
confidence: 68%
“…In particular, it has been shown that methylammonium iodide sublimes in vacuum, leading to the formation of lead iodide (Deretzis et al, 2015;Juarez-Perez et al, 2018;Alberti et al, 2019). Exposure to vacuum has also been shown to lead to the formation of metallic lead in 3D perovskites (Gunasekaran et al, 2018) and to the reduction of photoluminescence (Fang et al, 2016;Tang et al, 2016). To date, the effect of vacuum on 2D perovskites remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 114,143,144 ] Under some aging stresses, such as light irradiation, [ 4 ] moisture, [ 145 ] and thermal stress, [ 108 ] the perovskite material is prone to degradation to generate PbI 2 and other fragments because of its low dissociation energy. [ 146 ] Qin et al first illuminated the trap‐induced degradation mechanism of PSCs. A large number of hole traps were found in the PSC degraded by continuous illumination, and Pb 0 defects have the potential to form hole traps.…”
Section: Various Types Of Defectsmentioning
confidence: 99%
“…Perovskite refers to a three‐dimensional (3D) structure for a class of materials with chemical formula ABX 3 (A and B are the cations and X is oxygen or halide) . Perovskites that form with the organic and inorganic constituents are known as hybrid organic‐inorganic perovskites (HOIPs) . Due to extraordinary optical properties, for example, emission, absorption, and tunable optical band gap (visible to infrared), the HOIPs materials are mostly used for photovoltaic applications .…”
Section: Introductionmentioning
confidence: 99%
“…Due to extraordinary optical properties, for example, emission, absorption, and tunable optical band gap (visible to infrared), the HOIPs materials are mostly used for photovoltaic applications . The properties of perovskite materials can be varied by replacing A, B, or X sites with a suitable protonated organic molecule, divalent metal cations, and halogens, respectively . A representative structure of HOIPs is shown in Figure .…”
Section: Introductionmentioning
confidence: 99%